Q: What is 3x2 x 2x5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2x5) x (55x56) ÷ 6 = 10 x 55 x 56/6 = 10 x 55 x 28/3 = 15400/3 = 5133.3333 It is the required answer.

3x2 - 7x + 2 = 3x2 - 6x - x + 2 = 3x(x - 2) - 1(x - 2) = (3x - 1)(x - 2) So x = 1/3 or x = 2

3x2 + 48 + 192 = 3x2 + 240 = 3 (x2+ 80)

If you meant 3x2 - 5x + 2, here is your answer 3x2 - 5x +2 = 0 => 3x2 - 3x - 2x + 2 = 0 => 3x(x-1) - 2(x-1) = 0 => (3x - 2) (x-1) = 0 => x = 2/3 or, x = 1

-2 x 5 = -10

Related questions

A factor tree of 75,000 is 75,000 75 x 1000 (3 x 25) x (10 x 100) (3 x (5x5)) x ((2x5) x (10x10)) (3 x (5x5)) x ((2x5) x ((2x5)x(2x5))) So, the prime factorization is 2 x 2 x 2 x 3 x 5 x 5 x 5 x 5 x 5 = 23 x 3 x 55

they are telling u that X=5, so plug in a 5 anywhere there is an X, so now is 52 x 2x5= 5x5=25 , so now is: 25x(2x5), 2x5=10, so now is 25x10=250 ,so the answer is : x2x (2x) = 52x(2x)=52x(2x5)=25x2x5=250

It is not an equation it is an expression but if it was in the form of 4-x-3x2 = 0 then 3x2 by itself:- 3x2 = 4 -x

(2x5) x (55x56) ÷ 6 = 10 x 55 x 56/6 = 10 x 55 x 28/3 = 15400/3 = 5133.3333 It is the required answer.

3x3 - x2 - x - 1 = 3x3 - 3x2 + 2x2 - 2x + x - 1 = 3x2(x - 1) + 2x(x - 1) + 1(x - 1) = (3x2 + 2x + 1)(x - 1) So 3x3 - x2 - x - 1 /(x - 1) = (3x2 + 2x + 1)

3x2 - 7x + 2 = 3x2 - 6x - x + 2 = 3x(x - 2) - 1(x - 2) = (3x - 1)(x - 2) So x = 1/3 or x = 2

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x + 2) - 4(x + 2) = (x + 2)(3x - 4).

Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)

x3 - 3x2 + x - 3 = (x - 3)(x2 + 1)

3x2-2x-21 = (3x+7)(x-3)

3x2-9x-30 =3x2+6x-15x-30 =3x(x+2)-15(x+2) =(3x-15)(x+2) OR 3(x - 5)(x+2)